Navigating Infrastructure Crises: Trans-theoretical Leadership and Pedagogical Identity Transformation in Indonesian Pioneer - Puspitasari, Thalia Yasmin; RASHYASIH, YAYAH; DIKDIK , ASEP (Edukasi, 2025)
Pioneer schools in Indonesia face infrastructure crises that impede learning quality. However, research on adaptive leadership strategies under such resource constraints remains limited. This study aimed to explore the implementation of trans-theoretical leadership as a strategic response to infrastructure crises and examine its impact on pedagogical identity transformation in pioneer schools. A phenomenological case study was conducted at SMPN 5 Cileunyi, involving six informants through in-depth interviews, participant observation, and document analysis. Data were analyzed using thematic analysis and interpretative phenomenological analysis supported by ATLAS.ti 24. Network analysis using ATLAS.ti revealed distinct stakeholder-specific code patterns distributed across 6 stakeholder categories, demonstrating interconnectedness among major themes. Three major themes emerged: the infrastructure crisis acting as a catalyst for organizational transformation, with crisis experience serving as a central organizing principle; the simultaneous integration of four leadership styles across stakeholder groups; and the reconstruction of collective pedagogical identity through cross-stakeholder collaboration. This study also revealed three empirical paradoxes: resource scarcity enhances creativity, informal structures strengthen coordination, and external pressure increases team cohesion. Trans-theoretical leadership manifests as a crisis-induced leadership ecosystem that transforms adversity into collective adaptive capacity. These findings contributed to the development of crisis-induced leadership evolution theory and provided practical frameworks for pioneering school management. Moreover, the ecosystem leadership model can be adapted for other pioneering schools through network-based interventions that focus on hub strengthening and bridge building.